Morphosyntax in children with word finding difficulties. - Murphy, V; Dockrell, J; Messer, D; Farr, H (2008)
Children with word finding difficulties (CwWFDs) are slower and less accurate at naming monomorphemic words than typically developing children (Dockrell, Messer and George, 2001), but their difficulty in naming morphologically complex words has not yet been investigated. One aim of this paper was to identify whether CwWFDs are similar to typically developing children at producing inflected (morphologically complex) words. A second aim was to investigate whether the dual-mechanism model could account for the use of morphology in a sample of CwWFDs, exemplifying the notion that regular inflections are part of a rule-based system and computed on-line, while irregular inflections are retrieved directly from the associative system (Pinker, 1999). The inflectional knowledge of a group of CwWFDs was compared against a group of language age-matched typically developing peers in three experiments. In Experiment 1 children produced the past tenses of high- and low-frequency regular and irregular English verbs. In Experiment 2 children generalized their knowledge of the past tense system onto nonsense verbs and in Experiment 3 children produced past tenses of verbs used in either a denominal or a verb root context. In each of these three studies, the CwWFDs performed similarly to matched typical children, suggesting that they do not have a selective problem with morphosyntactic features of words. The findings provide mixed support for the dual-mechanism model.